2019
DOI: 10.1103/physrevx.9.041046
|View full text |Cite
|
Sign up to set email alerts
|

Structural Invertibility and Optimal Sensor Node Placement for Error and Input Reconstruction in Dynamic Systems

Abstract: Despite recent progress in our understanding of complex dynamic networks, it remains challenging to devise sufficiently accurate models to observe, control or predict the state of real systems in biology, economics or other fields. A largely overlooked fact is that these systems are typically open and receive unknown inputs from their environment. A further fundamental obstacle are structural model errors caused by insufficient or inaccurate knowledge about the quantitative interactions in the real system.Here… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(33 citation statements)
references
References 67 publications
0
33
0
Order By: Relevance
“…Specifically, we choose x c from x so that the resulted system is close to be invertible [40]. If a system is invertible, for a given value of x 0 , unique values of y will correspond to unique values of inputs, so one could reconstruct the values of inputs from available output measurements [41,42]. If w c in the hybrid model (Eqs 5b and 5c) is viewed as an input to the system and the hybrid model is invertible, the values of w c can be uniquely characterized from given measurements [41,43].…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…Specifically, we choose x c from x so that the resulted system is close to be invertible [40]. If a system is invertible, for a given value of x 0 , unique values of y will correspond to unique values of inputs, so one could reconstruct the values of inputs from available output measurements [41,42]. If w c in the hybrid model (Eqs 5b and 5c) is viewed as an input to the system and the hybrid model is invertible, the values of w c can be uniquely characterized from given measurements [41,43].…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…In nearly all cases we have to deal with the presence of unknown structural model errors . We call these model errors structural , for they can lie in the functional form or in the very network topological structure of a system and can not be fixed by adjusting the parameters, compare (Engelhardt et al, 2016 , 2017 ; Kahl et al, 2019 ; Villaverde et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Algorithms for recovering the errors of a given model (1) from data implicitly assume that the root cause for an error can uniquely be identified (Kolodziej and Mook, 2005 ; Engelhardt et al, 2016 , 2017 ; Villaverde et al, 2019 ; Newmiwaka et al, 2020 ). However, this uniqueness assumption is often violated because the output function c does not provide sufficient information (Engelhardt et al, 2016 ; Kahl et al, 2019 ) about the root cause for the observed discrepancy y − y data between model and data. Based on the representation of model errors as unknown inputs (Kolodziej and Mook, 2005 ; Engelhardt et al, 2016 ) to the system (1), it was possible to relate the problem of error reconstruction to the problem of system invertibility (Kahl et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations